Ectopic pregnancy with fetal mummification in a female dog: Case report - Silveira, Dyego Deleon Mendes da; Gomes, Caroline Ribeiro; Mota, Nayane dos Reis; Silva, Iara Souza; Barbosa, Vivian de Brito; Aguiar, Thais Pereira; Medina, Dandara Campos Dirino; Paula, Mhaique Henrique de; Hamade, Vanessa do Carmo Eleto; Sá, Roger Richelle Bordone de (Pubvet, 2024)
Ectopic pregnancy is a condition where the fetus develops in atypical locations, whether intrauterine or extrauterine. Among the forms of ectopic pregnancy, secondary abdominal pregnancy is the most described in the literature. It develops as a consequence of trauma that causes uterine rupture. The aim of this study is to report a case in which a patient, with a history of trauma due to a car accident, presented a mummified fetus in the abdominal cavity. The patient was admitted with a complaint of dystocia and, after a C-section, an ovariohysterectomy was performed. During inspection of the abdominal cavity, a mummified fetus, enveloped by the omentum, was identified and carefully removed, separating the attached structures. During the ovariohysterectomy procedure, no macroscopic signs of scarring were observed in the uterus. The patient and her puppies did not present any complications during or after the procedure, and the adopted approach was effective, resulting in a normal birth for the puppies and a complication-free postoperative period for the mother.